Descarte de fêmeas suínas em granjas de quarto sítio e em unidades produtoras de leitões com reposição de leitoas gestantes: eficiência reprodutiva e validação das razões atribuídas para o descarte - Ulguim, Rafael da Rosa (2011)
In conventional swine production systems, with acquisition of replacement gilts either from commercial suppliers or internal replacement, high culling rates are associated with reduced productive efficiency. The culling pattern of alternative replacement systems, consisting of four-site units (4S) that prepare replacement gilts to be sold pregnant to piglet-production units (PP) are not yet characterized. The objectives of this study are: to characterize the culling pattern and the associations between the culling reasons and female reproductive efficiency in 4S and PP units; and to associate culling reasons recorded at farm level with examining genital organs of culled females at a slaughterhouse. Individual female records of culled females (n = 5,013) were extracted from databases of three 4S units and ten PP units. A frequency distribution was generated for the culling reasons, which were classified as: reproductive failure, low productivity, age, locomotor problems; and other causes. The evaluated parameters of reproductive efficiency were: herd lifetime; non productive days (NPD); and total number of piglets born during herd lifetime (PBL), per parity (PBP) and per year of herd lifetime (PBY). Such parameters were compared according to the production units, parity at culling (PC) and culling reason. At the slaughterhouse, the uterus and the ovaries of 311 culled females from the same 13 units were evaluated. Culling for locomotor problems was more frequent in 4S units, whereas culling for low productivity was more frequent in PP units. In 4S units, herd lifetime was 71.8 ± 0.8 d and the first service to culling interval was 57.1 ± 0.8 d. In the PP units, herd lifetime was 672.5 ± 7.1 d and PC was 4.4 ± 0.1. Parameters related to piglets production over time were similar to those observed in conventional production systems, with the lowest PBL (33.5 ± 1.1) observed for females culled for reproductive failure and PBY (22.8 ± 0.3) for those culled for productivity. At the slaughterhouse evaluation, the frequency of ovaries presenting cysts and no structures were 12.6% and 10.9%, respectively. No association was observed among such pathologies and the reproductive failures recorded as the reasons for female culling (P > 0.05). The production system combining 4S and PP units presented PC somewhat increased and decreased NPD, in comparison with conventional replacement systems, indicating a potential for increasing female retention rates and reducing the impact of premature female culling on herd reproductive efficiency.